Effect of rice husk biochar and chicken dung as soil amendment for improvement of soil chemical properties and growth performance of Phyllantus niruri (dukung anak) in an organic cultivation system - Mat Zain, Norma (2015)
Phyllantus niruri is one of the highly demanded herbs in Malaysia for treating diabetes, wounds, scabies, kidney stone and ringworm. The herb production rate is still low due to small scale planting and most of Malaysian soil is infertile because the soil is highly weathered acidic soil. P. niruri is planted in an organic system due to highly demand of alternative medicine. Organic system can assure the herbs to become a safe and uncontaminated product. Besides that, the global demand for organically sustainable production herbs also increases. Thus, the infertile soil needs to be improved with the addition of organic amendment to improve herb’s growth for increasing biomass production in a larger scale. So, rice husk biochar and chicken dung is a potential soil amendment to improve soil fertility. Biochar is a charcoal that is produced through pyrolysis. It has been reported that the benefits of biochar addition to soil is that it has the ability to retain nutrients, high stability against decay, able to remove carbon dioxide from the atmosphere, and revitalize degraded grounds. Chicken dung is used because it is easily available and commonly used by farmer as amendment for rapid improvement of soil in growing vegetables. A study was conducted to determine the effect combination of biochar and chicken dung application to soil chemical properties and growth performance of P. niruri. The experiment was conducted under shelter. There were 9 treatments (0 tan/ha, 5 tan/ha, and 10 tan/ha of biochar and 0 tan/ha, 2.5 tan/ha, and 5 tan/ha of chicken dung respectively) and 4 replications. Treatments were arranged in Randomized Complete Block Design (RCBD). The soil used was taken from Ladang 16, UPM. Different rates of biochar and chicken dung were used to determine the most suitable rate to improve soil chemical properties that give optimum herb yield. Parameters such as plant height, plant canopy diameter, and number of branches were taken every 2 weeks after planting. After harvesting in the eighth week of planting, total plant biomass, plant fresh weight and dry weight were determined. Plant samples were analyzed for total N, P, K, Ca and Mg. The soil samples were analyzed for pH, available P, CEC, total C, total N, and exchangeable bases (K, Ca, and Mg). The results obtained showed that there were significant difference between control and treatments of plant growth parameter, plant nutrient uptake and soil chemical properties.